Pelatihan Pembuatan Pupuk Kompos Kulit Kacang Tanah Pada Ibu-Ibu Anggota Dasawisma Jambu PKK Gabahan RT. 05 RW. 12 Jombor Sukoharjo - Nur Rokhimah Hanik; Tri Wiharti; Ratna Dewi Eskundari (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Most of the PKK dasawisma Jambu women in the hamlet of Gabahan RT 05 RW 12 are new residents with a new home environment that is in the stage of structuring new gardens and ornamental plants. And most of them work as housewives who need to get skills that can increase family income. They have never received counseling or training on making organic compost by universities or other institutions. From the results of the interview, several residents wanted counseling and training on the manufacture of organic compound fertilizer as an alternative to increase financial income. For this reason, the Abdimas Team of Biology education study program will give it to the residents of Gabahan village, RT. 05 RW. 12 Jombor about making organic compost. They want counseling with this theme because most of them do not understand how to make organic compost. The purpose of the service is 1. To provide counseling on how to make organic compost. 2. To provide training/skills in packaging organic compost fertilizers.The training was carried out for 3 times. The method used is lectures and questions and answers, as well as practical guidance on how to make and pack organic compost. The target of this counseling and training is to increase the understanding of how to make 20% organic compost among the residents of Gabahan RT. 05 RW. 12 Jombor. From the results of the training on making organic compost for the women members of the Jambu PKK dasawisma Gabahan RT 05 RW 12 Jombor, it can be concluded that there was an increase in understanding of the process of making organic compost from an average score of 56.8 to 85.5 or an increase in understanding of Rp. 33.2%. The results of the compost can be used by women as plant fertilizer, but can also be sold to increase income.